Private power and political rationality: theoretical perspectives for a resistance criminology (Delito y Sociedad, 2022)
This article aims to analyze the theoretical perspectives on private power and political rationality offered by Foucault and Ferrajoli, taking into account the categories of social harm and violence. Based on this, this article will delineate some neoliberalism´s characteristics, as a political rationality currently constituted in a global and hegemonic way, and will investigate aspects of the US invasion of Iraq in 2003 as an example of the exercise of private power. This will allow to rethink the constitution of criminology as a discipline of criticism and resistance against the exercise of power.
Keywords: criminology; private power; political rationality